The Morphological Changes in the Capillary Architecture of the Tibial Nerve Associated with Spontaneous Aging and Aerobic Exercise Intervention during Aging in Rats - Sakita, Masahiro (The Society of Physical Therapy Science, 2014)
[Purpose] Peripheral nerve degradation associated with aging is linked to failure of interactions in capillary metabolism. The aim of this study was to morphologically investigate the age-related changes in the capillary architecture of the tibial nerve in spontaneous aging and with aerobic exercise intervention in rats. [Subjects] Male Sprague-Dawley rats (n=15) were used in the present study. [Methods] The rats were divided into control (Cont, n=5), elderly (Elder, n=5), and elderly with aerobic exercise (Elder+Ex, n=5) groups. Aerobic training of low intensity was performed for 10 weeks using a treadmill starting at 96 weeks of age by the Elder+Ex group. The capillary diameter, cross-sectional area and number of microvascular ramifications in the tibial nerve were compared among the Cont (20-week-old), Elder (106-week-old) and Elder+Ex groups using three-dimensional images gained from confocal laser scanning microscopy. [Results] The capillary diameter, cross-sectional area and number of microvascular ramifications in the Elder group were significantly smaller than those observed in the Cont and Elder+Ex groups. [Conclusion] These findings suggest that the capillaries in the peripheral nerve degrade with spontaneous aging and that aerobic exercise of low intensity promotes angiogenesis, and protects the capillary from oxidative stress.